State-of-the-art etiology and pathogenesis of dry eye - E.B. Tatarnikova; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
State-of-the-art etiology and pathogenesis of dry eye E.B. Tatarnikova, O.I. Krivosheina Siberian State Medical University, Tomsk, Russian Federation Numerous studies on the causes, diagnosis, and treatment for dry eye are now underway worldwide. Current tendency is accounted for by growing prevalence, no common conception of the development, and inadequate efficiency of available treatment for dry eye. Dry eye manifests by ocular discomfort and dryness, blurred vision, and sensitivity to wind and smoke. A constant (and sometimes lifelong) need for ocular lubricants is an important limitation of pharmacotherapy for this disease. Surgery is associated with the risk of corneal and conjunctival damage and postoperative infections. Therefore, novel treatment approaches as well as in-depth study of dry eye etiology and pathogenesis are required. This article reviews domestic and foreign publications highlighting recent data on dry eye prevalence in various population groups, its risk factors, and background. Major pathogenic mechanisms of dry eye are also discussed. Detailed information on the causes and mechanisms of the develo pment of dry eye contributes to the diagnosis and, as a result, early treatment and prevention. Keywords: dry eye, tear film, hyperosmolarity, neurosensory mechanisms, oxidative stress. For citation: Tatarnikova E.B., Krivosheina O.I. State-of-the-art etiology and pathogenesis of dry eye. Russian Journal of Clinical Ophthalmology. 2020;20(3):128–132. DOI: 10.32364/2311-7729-2020-20-3-128-132.